2002
DOI: 10.2486/indhealth.40.28
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Cardiovascular Risk Correlates of Serum Triglycerides in Young Japanese Adults.

Abstract: To examine the distribution and cardiovascular risk correlates of serum triglycerides, a cross-sectional population study based on annual health examinations at the workplace was performed in 2199 young Japanese adults aged 23 to 37 years. Triglyceride levels showed significant sex (male > female) differences, and the percentages of those with high triglycerides (≥ 150 mg/dl) were 9.4% for males and 0.8% for females. In terms of conjoint trait of dyslipidemia, 86.1% of males displayed normal levels of both tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In this respect both LDL and triglycerides are believed to play, differentially, a key role in maintaining the quantity of serum cholesterol: LDL is the main cholesterol-rich lipoprotein in plasma (Thompson and Wilson, 1992) contributing to atherosclerotic plaguing (Fricchione et al, 1996;, while triglycerides are associated with a pattern of obesity, central adiposity and insulin resistance which can exert effects on blood pressure, the latter being an established CHD risk factor. It is generally accepted nowadays that attention to hypertriglyceridemia with respect to increased CHD risk represents an important step in assessing global risk for CHD development (Niaura et al, 2000;Nakanishi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect both LDL and triglycerides are believed to play, differentially, a key role in maintaining the quantity of serum cholesterol: LDL is the main cholesterol-rich lipoprotein in plasma (Thompson and Wilson, 1992) contributing to atherosclerotic plaguing (Fricchione et al, 1996;, while triglycerides are associated with a pattern of obesity, central adiposity and insulin resistance which can exert effects on blood pressure, the latter being an established CHD risk factor. It is generally accepted nowadays that attention to hypertriglyceridemia with respect to increased CHD risk represents an important step in assessing global risk for CHD development (Niaura et al, 2000;Nakanishi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A low fasting triglyceride level (ie, Ͻ100 mg/dL) is commonly found in underdeveloped societies and countries at low CVD risk (eg, Africa, China, Greece, and Japan), [361][362][363][364][365][366][367][368][369][370][371][372][373] as contrasted with the United States, where mean levels are Ϸ15% to 30% higher. 6 Consistent with a reduced likelihood of abnormal metabolic parameters (eg, IR) are observational studies and clinical trials 3,232,367,374 -380 that have consistently demonstrated the lowest risk of incident and recurrent CVD in association with the lowest fasting triglyceride levels.…”
Section: Defining Levels Of Risk Per the National Cholesterol Educatimentioning
confidence: 99%
“…6) HDL-C: high density lipoprotein cholesterol. 7) TG: triglyceride. 8) LDL-C: low density lipoprotein cholesterol.…”
mentioning
confidence: 99%